TAMAN SEMPUR DAN RUANG PUBLIK: Analisis Geo-Semiotik dan Etnografi - Justito Adiprasetio; Sandi Jaya Saputra (Program Studi Ilmu Komunikasi, 2018)
Since 2016, Public Park in Indonesia, particularly in West Java has significantly been revitalized. Taman Sempur is one of public parks located in West Java that spent about Rp 2.2 billion for its revitalization process. That massive amount was poured out in order to develop public space for the community. Taman Sempur is a compound where Taman Kaulinan, Taman Skateboard, Taman Ekspresi, big pedestrian and few sports facilities with its own specific functions stand. This research, that applied the combination of geo-semiotic and ethnographic analysis, attempted to observe how meaningful Taman Sempur as urban public space for the community through public space and public sphere approaches. The existing modality indicates that the community have certain attention to participate in Taman Sempur as public space, with some of its flaws in material dimension aspect. At the same time, public sphere nuances still vaguely felt, considering the community’s awareness were not full and even due to habitus individual conflict while becoming part of the “public”.Keywords: Taman Sempur, Urban Public Space, Public Sphere, Geo-Semiotic